Effects of disks on gravitational lensing by spiral galaxies - Bartelmann, Matthias; Leyb, Avraham (Arxiv, 2013)
Gravitational lensing of a quasar by a spiral galaxy should often be accompanied by damped Lyman-alpha absorption and dust extinction due to the intervening gaseous disk. In nearly edge-on configurations, the surface mass density of the gas and stars in the disk could by itself split the quasar image and contribute significantly to the overall lensing cross section. We calculate the lensing probability of a disk+halo mass model for spiral galaxies, including cosmic evolution of the lens parameters. A considerable fraction of the lens systems contains two images with sub-arcsecond separation, straddling a nearly edge-on disk. Because of that, extinction by dust together with observational selection effects (involving a minimum separation and a maximum flux ratio for the lensed images), suppress the detection efficiency of spiral lenses in optical wavebands by at least an order of magnitude. The missing lenses could be recovered in radio surveys. In modifying the statistics of damped Lyman-alpha absorbers, the effect of extinction dominates over the magnification bias due to lensing.